Prejudice: A Comparative Study of The Perspectives in Tafsir Al-Ibriz and Tafsir Fi Zilalil-Qur'an - Rahayu, Nur Jiyannah A; Mardiyana, Alfa (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2023)
Human beings are social creatures that require interactions among individuals. Encountering those who hold various prejudices towards individuals or different groups in their surroundings often leads to conflicts and animosity among fellow beings. Therefore, the presence of prejudices, whether positive or negative, significantly affects one's attitude and behavior in societal life. This study elucidates the commonalities and differences of prejudices as presented in the interpretations of Al-Ibrīz and Tafsīr Fī Ẓilālil-Qur'ān, and how prejudice is classified in contemporary society. The purpose of this research is to identify the similarities and disparities in prejudices as depicted in the interpretations of Al-Ibrīz and Tafsīr Fī Ẓilālil-Qur'ān, as well as to understand the classification of prejudices in modern society. The research employs a comparative method using the technique of library research, with Al-Ibrīz by Bisri Musthofa and Tafsīr Fī Ẓilālil-Qur'ān by Sayyid Quthb as the primary sources of reference. The findings of this study indicate: 1.) Both commentators share a similar interpretation of prejudice, which is the prohibition of harboring excessive prejudices, as some forms of prejudice are considered sinful. However, there is a difference in their interpretations. According to Bisri Musthofa, engaging in prejudice by seeking out others' faults and flaws can lead to slander. On the other hand, according to Sayyid Quthb, it is advised not to be easily swayed by conjectural whispers and to strive to eliminate slander to preserve the bond of brotherhood among people. 2.) Prejudice is prevalent in societal life. As individuals engage in the world of social interaction, they are bound to encounter numerous instances where various types of prejudices, both positive and negative, are ingrained.